2014
DOI: 10.1016/j.cell.2013.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Priming of Memory Updating during Reconsolidation to Attenuate Remote Fear Memories

Abstract: Summary Traumatic events generate some of the most enduring forms of memories. Despite the elevated lifetime prevalence of anxiety disorders, effective strategies to attenuate long-term traumatic memories are scarce. The most efficacious treatments to diminish recent (i.e., day-old) traumata capitalize on memory updating mechanisms during reconsolidation that are initiated upon memory recall. Here, we show that, in mice, successful reconsolidation-updating paradigms for recent memories fail to attenuate remote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
315
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 326 publications
(340 citation statements)
references
References 70 publications
23
315
1
1
Order By: Relevance
“…It is currently not clear whether this within-session extinction also persists between sessions, but this would be worthy of future investigation. Consistent with this suggestion, previous research has shown that inhibition of Class I HDACs can enhance fear extinction memory (Bahari-Javan et al, 2012;Bredy and Barad, 2008;Graff et al, 2014;Lattal et al, 2007;Stafford et al, 2012;Whittle et al, 2013). Although systemic pharmacological HDAC3 inhibition fails to enhance cued fear extinction (Bowers et al, 2015), site-specific HDAC3 inhibition restricted to the hippocampus or amygdala might reveal an important role of HDAC3 in fear extinction memory.…”
Section: Discussionsupporting
confidence: 62%
“…It is currently not clear whether this within-session extinction also persists between sessions, but this would be worthy of future investigation. Consistent with this suggestion, previous research has shown that inhibition of Class I HDACs can enhance fear extinction memory (Bahari-Javan et al, 2012;Bredy and Barad, 2008;Graff et al, 2014;Lattal et al, 2007;Stafford et al, 2012;Whittle et al, 2013). Although systemic pharmacological HDAC3 inhibition fails to enhance cued fear extinction (Bowers et al, 2015), site-specific HDAC3 inhibition restricted to the hippocampus or amygdala might reveal an important role of HDAC3 in fear extinction memory.…”
Section: Discussionsupporting
confidence: 62%
“…All these data suggest that HDAC1 and HDAC2 contribute to the secondary functional loss after stroke. HDAC2 is an isoform negatively regulating cell survival (Nott et al, 2008) and neuronal plasticity (Gräff et al, 2014). In contrast, HDAC1 gain of function has a potent protection effect against neurotoxicity in vivo model for ischemia (Kim et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Histone deacetylases (HDACs) target histones, regulate chromosome dynamics, control cellular gene expression (Robert et al, 2011), and contribute to multiple signaling pathways linked to neuronal plasticity (Gräff et al, 2014), cell survival (Nott et al, 2008), neuroinflammation (Bie et al, 2014), and oxidative stress (Shimazu et al, 2013;Peng et al, 2015). Thus, HDACs may play a critical role in mediating pathophysiological events in the periinfarct area after stroke.…”
Section: Introductionmentioning
confidence: 99%
“…In the same year, Misanin et al (1968) suggested that consolidated memories become labile and susceptible to modulation when they are reactivated; that is, when they are evoked, they must undergo a new stabilization process to persist (Nader et al 2000;Sara 2000;de la Fuente et al 2011;Gräff et al 2014). This new stabilization process has been termed "reconsolidation" (Przybyslawski et al 1999).…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%